2021
DOI: 10.1093/neuonc/noab196.523
|View full text |Cite
|
Sign up to set email alerts
|

Nimg-23. Machine Learning Methods in Glioma Grade Prediction: A Systematic Review

Abstract: PURPOSE Machine learning (ML) technologies have demonstrated highly accurate prediction of glioma grade, though it is unclear which methods and algorithms are superior. We have conducted a systematic review of the literature in order to identify the ML applications most promising for future research and clinical implementation. MATERIALS AND METHODS A literature review, in agreement with PRISMA, was conducted by a university … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Our research group has also performed systematic reviews on the role of ML in predicting glioma grade and differentiating gliomas from brain metastases. 48,49 Both studies found, similar to our findings, a high mean accuracy despite small data sets. Overall, these findings are encouraging because they show that even though PCNSL is a rarer disease than other brain neoplasms, the development of ML applications for its diagnosis is on a par with that for other tumor entities.…”
Section: Discussionsupporting
confidence: 91%
“…Our research group has also performed systematic reviews on the role of ML in predicting glioma grade and differentiating gliomas from brain metastases. 48,49 Both studies found, similar to our findings, a high mean accuracy despite small data sets. Overall, these findings are encouraging because they show that even though PCNSL is a rarer disease than other brain neoplasms, the development of ML applications for its diagnosis is on a par with that for other tumor entities.…”
Section: Discussionsupporting
confidence: 91%